New records of Gymnopogon doellii (Poaceae, Chloridoideae, Cynodonteae, Hubbardochloinae), a Brazilian endangered species - Vinícius-Silva, Ronaldo; de Paula, Cláudio Coelho; Saraiva, Diogo Felcar (Phytotaxa, 2020)
We report new occurrence records of Gymnopogon doellii in Brazil, based on collections from the Ferruginous Campos Rupestres (rocky outcrops) of Minas Gerais state, in the southeastern region of the country. This native grass had been previously reported in Brazil only from Cerrado areas of Minas Gerais and Goiás states and the Federal District. According to the IUCN criteria, the species is endangered. Within the genus, G. doellii is distinguished by having short rhizomes, indistinct leaf blade midveins, ligules with a fringe of hairs and acuminate glumes twice the size of the floret. We provide photographs of individuals in the field, an illustration with details of the species morphology and an updated geographic distribution map.